2013
DOI: 10.4028/www.scientific.net/amr.837.271
|View full text |Cite
|
Sign up to set email alerts
|

Application of New Synthesized Materials Based on Anionic Clays for Industrial Effluent Decoloration

Abstract: This work reports hydrotalcite and zinc-substituted hydrotalcite (MeAlLDHs) anionic clays as novel catalytic formulations for some environmental applications regarding specific industrial coloured effluents. In this context, layered double hydroxides, covered or with tailored compositions, were synthesized, characterized using advanced analytical analysis techniques (XRD, FTIR, SEM) and tested in specific environmental applications. More specifically, LDHs samples were tested as catalysts for different treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A high number of research works reported that various solid materials can adsorb different organic substances (e.g., dyes, alcohols, amino acids, polymers, persistent organic compounds etc. ), heavy metal ions, and other contaminants from different industrial effluents by adsorptive processes of physical (physical adsorptions), chemical (chemisorptions) or biological nature (biosorptions), or mixed/hybrid adsorptive processes of all these, respectively [5][6][7][8][9][10][11][12]. From cost-efficiency and performance reasons, the cheap adsorbents which contain high quantities of carbon in their chemical structure, available in nature, or as production wastes, can remove different polluting loads from effluents (especially, industrial effluents), and recover useful retained species from the high adsorptive material due to its simple regeneration capacity.…”
Section: Virtual Reality Application Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A high number of research works reported that various solid materials can adsorb different organic substances (e.g., dyes, alcohols, amino acids, polymers, persistent organic compounds etc. ), heavy metal ions, and other contaminants from different industrial effluents by adsorptive processes of physical (physical adsorptions), chemical (chemisorptions) or biological nature (biosorptions), or mixed/hybrid adsorptive processes of all these, respectively [5][6][7][8][9][10][11][12]. From cost-efficiency and performance reasons, the cheap adsorbents which contain high quantities of carbon in their chemical structure, available in nature, or as production wastes, can remove different polluting loads from effluents (especially, industrial effluents), and recover useful retained species from the high adsorptive material due to its simple regeneration capacity.…”
Section: Virtual Reality Application Simulationmentioning
confidence: 99%
“…The colour of textile wastewater was expressed by the absorbance under a blank with distillate water at the three characteristic wavelengths (436, 525 and 620 nm) as in SR ISO 7887-97 standard, or by the Hazen color index which represents the conversion of absorbance at 456 nm into Hazen units [HU] (i.e. 0.069 (A 456 ) corresponds to 50 [UH])[5][6][7][8][9][10][11]. For industrial wastewater is obligatory measuring of absorbance at 436 nm in supernatant (apparent color) or filtrate (real color).…”
mentioning
confidence: 99%